The behavior of a co-flow structure to screen projects in a product pipeline - Figueiredo, Paulo Soares (2018)
Submitted by Núcleo de Pós-Graduação Administração (npgadm@ufba.br) on 2018-03-12T20:19:56Z No. of bitstreams: 1 The behavior of a co-flow structure to screen projects in a product pipeline.pdf: 1301298 bytes, checksum: 3e302c61acf387c7f67664749cd54eaf (MD5)